Predictive analysis on depression among university students in Bangladesh - Ahmed, Syed Aref; Mustafa, Khondokar Jamal E; Arif, Ibtesum; Tahmid, MD. Nafis (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.